2015
DOI: 10.1039/c5nr00582e
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous effects of surface spins: rarely large coercivity, high remanence magnetization and jumps in the hysteresis loops observed in CoFe2O4nanoparticles

Abstract: Well-dispersed uniform cobalt ferrite nanoparticles were synthesized by thermal decomposition of a metal-organic salt in organic solvent with a high boiling point. Some of the nanoparticles were diluted in a SiO2 matrix and then the undiluted and diluted samples were characterized and their magnetic behavior explored. The undiluted and diluted samples exhibited maximum coercivity Hc of 23,817 and 15,056 Oe at 10 K, respectively, which are the highest values reported to date, and the corresponding ratios of rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 43 publications
0
42
1
Order By: Relevance
“…The surface to volume ratio becomes also high with the decrease in particle size. 27,28 It is also observed that the M s value of bare (y = 0) nanoparticles is greater than coated nanoparticles which is due to their large average crystallite size of uncoated nanoparticles as compared to coated nanoparticles. 29 Similar phenomenon was also reported for NiFe 2 O 4 and CoFe 2 O 4 ferrite nanoparticles.…”
Section: -4 Kamran Et Almentioning
confidence: 71%
“…The surface to volume ratio becomes also high with the decrease in particle size. 27,28 It is also observed that the M s value of bare (y = 0) nanoparticles is greater than coated nanoparticles which is due to their large average crystallite size of uncoated nanoparticles as compared to coated nanoparticles. 29 Similar phenomenon was also reported for NiFe 2 O 4 and CoFe 2 O 4 ferrite nanoparticles.…”
Section: -4 Kamran Et Almentioning
confidence: 71%
“…The undiluted 9- and 13-nm NPs, i.e., H9 and H13, as well as the 16-nm NPs reduced at 300 °C (LT16) have the H c values of 20.0, 18.8, and 20.5 kOe at 10 K, smaller than 23.8 kOe (10 K) for our previously reported 10.7-nm CoFe 2 O 4 NPs [32] which particle size is close to the critical size of a single domain [33]. These H c values are much larger than that for the bulk CoFe 2 O 4 (6.8 kOe at 10 K) [34], because on the one hand, the particles are approximately single-domain sized, and on the other hand, the interaction between surface spins induces extra anisotropy and hence enhances H c , which will be further discussed below.…”
Section: Resultsmentioning
confidence: 91%
“…It is indicated that, in this temperature region, the dipolar interaction between the nanoparticles is prevailing [25]. Whereas, the FC curves present a small increase below about 16K, which is caused by the orientation of surface spins in the direction of the applied field [26]. Table 1 lists the S BET of the as-synthesized samples.…”
Section: Resultsmentioning
confidence: 94%